Fact versus feeling: What post-truth scholarship can learn from the feminist phenomenology of affect. (February 2023) - Harris, Erica
Although it is a relatively new phenomenon, the most popular descriptions of post-truth operate within the boundaries of the classical dichotomy between emotion and reason that dates back to Plato's Phaedrus : both, to some extent, view emotions as impediments to knowledge and our ability to live morally upstanding lives (248a-b). Post-truth, which is seen as a threat to reason, social cohesion, and fact-based knowledge claims, is either viewed as the outcome of the failure of our cognitive apparatus, or a consequence of our unchecked thirst for stories that provoke dramatic feelings. From a feminist point of view, this should give us pause, since the arguments used to dismiss post-truth resemble those that dismissed women's experiences and emotions as idiosyncratic or irrational. Have post-truth scholars been too hasty in their judgment of emotion-based knowledge claims? In this essay, I explore the transcendental role of emotion in its relationship to epistemic knowledge claims and argue that emotion should be given a more primordial status in the analysis of post-factuality. I do this by exploring the psychoanalytic and phenomenological analysis of affect, especially Sara Ahmed's feminist phenomenology of embodiment.